2010
DOI: 10.1590/s0100-39842010000100013
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome do impacto do tornozelo na ressonância magnética: ensaio iconográfico

Abstract: A síndrome do impacto do tornozelo é uma condição dolorosa causada por atrito de tecidos articulares, que é tanto causa quanto consequência de uma biomecânica alterada desta articulação. A sua principal causa são as lesões pós-traumáticas, principalmente lesões ligamentares, resultando em dor crônica no tornozelo. Do ponto de vista anatômico e clínico, estas síndromes são classificadas em: ântero-lateral, anterior, ântero-medial, póstero-medial e posterior. A ressonância magnética é um ótimo método diagnóstico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
0
4
0
3
Order By: Relevance
“…Articular pain may become a limiting factor and even a cause of disability in the patient's life, and may affect any joint in the human body (46,47) . The literature presents discordant information on the actual causes of pain in osteoarthritis patients, but recent multicentric studies, such as MOST (28,30) , have demonstrated the association between bone attrition and pain.…”
Section: Discussionmentioning
confidence: 99%
“…Articular pain may become a limiting factor and even a cause of disability in the patient's life, and may affect any joint in the human body (46,47) . The literature presents discordant information on the actual causes of pain in osteoarthritis patients, but recent multicentric studies, such as MOST (28,30) , have demonstrated the association between bone attrition and pain.…”
Section: Discussionmentioning
confidence: 99%
“…MRI findings are not pathognomonic, but capsular thickening, soft tissue thickening surrounding the ligaments, and generally low signal intensity in all pulse sequences, indicating fibrous tissue with distortion of the ankle gutters, is highly suspicious. [63][64][65] Pseudo-meniscoid lesions can be depicted with MRI. MR arthrography is helpful in doubtful cases.…”
Section: Osteochondral Lesionsmentioning
confidence: 99%
“…Similar relationships were found for the risk of depression and mood disorders in patients with persistent pain 3 . Pain may become a limiting and even disabling factor for patients and may affect any joint 4,5 . Several mechanisms and effects may be influenced by physiotherapy cognitive, physical and behavioral artifices, thus cooperating for the treatment of such patients 6 .…”
Section: Introductionmentioning
confidence: 99%